A framework for model based code generation - Basma Moukhtar Hussein; Akram Salah (Cairo : Basma Moukhtar Hussein, 2014)
The demand became high on the software production, and the production of high - quality software takes a lot of time. This makes the productivity a key concept in today's software industry and this turned the focus to the idea of automatic code generation. Automatic Code Generation is the process of generating code based on a specification automatically (using other programs) not manually. Model driven architecture (MDA), proposed by the object management Group (OMG), is a promising approach for developing applications, based on a platform-independent model (PIM) of the application or specification's business functionality and behavior and one or more platform specific models (PSMs). It separates the implementation details from business functions. Thus, it is not necessary to repeat the process of defining an application or system's functionality and behavior each time a new technology - Web Services, for example comes along
Thesis (M.Sc.) - Cairo University - Faculty of Computers and Information - Department of Computer Science
Issued also as CD
Keywords: Code generation; Model driven architecture; PIM